Developing EFL writing through project work (2009)
This project is an action research focused on the development of EFL writing in third graders of a public school in Bogotá. First of all based on the need analysis of children in primary who need to connect vocabulary with structures in an authentic and contextualized way, the implementation of project work was done involving different writing tasks in order to develop writing skills that let the students start writing for specific and communicative purposes .Through this research was found that the students started to write in EFL in a contextualized way through descriptive short compositions that the students were able to produce with the guide of copying strategy , carrying out a project that reflected about themselves and their family.